1995
DOI: 10.3109/00952999509095230
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Comparison of Bromocriptine and Placebo in Cocaine Withdrawal

Abstract: Twenty-nine cocaine-dependent male veterans without other drug dependence completed a double-blind controlled, randomly-assigned study examining the efficacy of bromocriptine versus placebo in the management of cocaine abstinence symptomatology. Serum prolactin (PL) and growth hormone (GH) levels were obtained prior to and after the study was completed. Patients were seen daily and completed several self-report questionnaires, including the Symptom Checklist-90-Revised, the Beck Depression Inventory, and a Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 16 publications
0
15
2
Order By: Relevance
“…Our results are in contrast to other investigators who reported no changes in PRL (Swartz et al 1990;Baumann et al 1995;Eiler et al 1995) or found lower PRL levels (Gawin and Kleber 1985) among cocaine abusers. Differences in sample characteristics and assay techniques may account for the inconsistencies in findings in the literature.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Our results are in contrast to other investigators who reported no changes in PRL (Swartz et al 1990;Baumann et al 1995;Eiler et al 1995) or found lower PRL levels (Gawin and Kleber 1985) among cocaine abusers. Differences in sample characteristics and assay techniques may account for the inconsistencies in findings in the literature.…”
Section: Discussioncontrasting
confidence: 86%
“…However negative results have also been reported. For example, in controlled and uncontrolled clinical trials with bromocriptine, plasma PRL was not correlated with intensity of withdrawal, symptom improvement or dropout rate in cocaine patients (Eiler et al 1995;Teller and Deveny 1988). Along the same lines, Satel et al (1991) found that PRL levels after cessation of cocaine use are not a good predictor of withdrawal severity and need for treatment in hospitalized cocaine patients.…”
Section: Introductionmentioning
confidence: 95%
“…Several classes of pharmaceutical agents have been studied in the treatment of patients with cocaine dependency (Hendelsman et al, 1995(Hendelsman et al, , 1997Eiler et al, 1995;Ehrman et al, 1996;Kampman et al, 1996;Margolin et al, 1995;Preston et al, 1992). Of the numerous agents studied, only the anticonvulsants have been shown to provide any ef®cacy in cocaine use reduction (Halikas et al, 1997;Margolin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research has focused largely on dopaminergic, serotonergic and noradrenergic compounds (Kosten et al 1987;Handelsman et al 1987;Berger et al 1989;Giannini et al 1989;Balon 1994;Eiler et al 1995;Margolin et al 1995), although to a lesser extent, lithium, opiate agonists and antagonists, and carbamazepine have also been explored Lemere, 1991;Cornish et al 1995;Kranzler et al 1995;Montoya et al 1995). Results from open clinical trials have sometimes been promising; however, double blind studies have generally been disappointing.…”
Section: Introductionmentioning
confidence: 96%